Investigation of the value of a photographic tool to measure self-perception of enamel opacities - Davies, Gill M (BioMed Central, 2012)
BACKGROUND: The standard measurement of oral conditions that are mainly of cosmetic concern can be carried out by a trained clinical professional, or they can be assessed and reported by the individuals who may have the condition or be aware of others who have it. Enamel opacities of anterior teeth are examples of such a condition. At a public health level the interest is only about opacities that are of aesthetic concern, so the need for an index that records opacities that the public perceive to be a problem is clear. Measurement methods carried out by highly trained professionals, using unnatural conditions are not indicated at this level. This study reports on the testing of a novel epidemiological tool that aims to report on the prevalence and impact of self-perceived enamel opacities in a population of young adolescents. METHODS: A dental health survey was carried out using a random sample of 12-year-old school pupils during 2008/09 by Primary Care Organisations (PCOs) in England. This included the use of a novel self-perception tool which aimed to measure individual’s self-perception of the presence and impact of enamel opacities to produce population measures. This tool comprised questions asking about the presence of white marks on their teeth and whether these marks bothered the volunteers and a sheet of grouped photographs of anterior teeth showing opacities ranging from TF 0, TF 1–2 to TF 2–3. Volunteers were asked which of the groups of photographs looked more like their own teeth. Examining teams from a convenience sample of 3 PCOs from this survey agreed to undertake additional measurements to assess the value of the self-perception tool. Volunteer pupils were asked the questions on a second occasion, some time after the first and clinical examiners recorded their assessments of the most closely matching set of photographs of the volunteers on two occasions. RESULTS: The tool was feasible to use, with 74% of pupils making a response to the first question about the presence of white marks on front teeth, 94% to the second (do these marks bother you?) and 79% to the third about which set of images most closely matched the volunteer’s own, with regard to white marks. Responses to these sequential questions showed coherence with pupils who perceived themselves as having white marks on their teeth being more likely to select images that showed teeth with opacities to match with their appearance. Pupils who reported themselves concerned about their white marks were the most likely to select images with the most severe opacities. Repeatability was good among pupils (Kappa = 0.65) and very good among examiners (Kappa = 0.87). Agreement levels between pupil’s and examiner’s choice of images was poor as examiners were less likely than pupils to select images that showed more severe levels of mottling. CONCLUSIONS: With regard to feasibility, coherence and repeatability the standardised epidemiological tool under scrutiny, with operator training, appears to be a suitable method for measuring the prevalence and impact of self-perceived enamel opacities in a population of young adolescents.